Dietary and Flight Energetic Adaptations in a Salivary Gland Transcriptome of an Insectivorous Bat - Phillips, Carleton J.; Phillips, Caleb D.; Goecks, Jeremy; Lessa, Enrique P.; Sotero-Caio, Cibele G.; Tandler, Bernard; Gannon, Michael R.; Baker, Robert J. (PloS one, 2014)
We hypothesized that evolution of salivary gland secretory proteome has been important in adaptation to insectivory, the most common dietary strategy among Chiroptera. A submandibular salivary gland (SMG) transcriptome was sequenced for the little brown bat, Myotis lucifugus. The likely secretory proteome of 23 genes included seven (RETNLB, PSAP, CLU, APOE, LCN2, C3, CEL) related to M. lucifugus insectivorous diet and metabolism. Six of the secretory proteins probably are endocrine, whereas one (CEL) most likely is exocrine. The encoded proteins are associated with lipid hydrolysis, regulation of lipid metabolism, lipid transport, and insulin resistance. They are capable of processing exogenous lipids for flight metabolism while foraging. Salivary carboxyl ester lipase (CEL) is thought to hydrolyze insect lipophorins, which probably are absorbed across the gastric mucosa during feeding. The other six proteins are predicted either to maintain these lipids at high blood concentrations or to facilitate transport and uptake by flight muscles. Expression of these seven genes and coordinated secretion from a single organ is novel to this insectivorous bat, and apparently has evolved through instances of gene duplication, gene recruitment, and nucleotide selection. Four of the recruited genes are single-copy in the Myotis genome, whereas three have undergone duplication(s) with two of these genes exhibiting evolutionary 'bursts' of duplication resulting in multiple paralogs. Evidence for episodic directional selection was found for six of seven genes, reinforcing the conclusion that the recruited genes have important roles in adaptation to insectivory and the metabolic demands of flight. Intragenic frequencies of mobile- element-like sequences differed from frequencies in the whole M. lucifugus genome. Differences among recruited genes imply separate evolutionary trajectories and that adaptation was not a single, coordinated event.